Improving Acne Self-Medication among Adolescents through Skin Health Education at Al-Istiqomah Islamic Boarding School - Genialita Fahdilla; Risa Susanti; Rosa Rosmawati (Fakultas Kewirausahaan Universitas Garut, 2026)
Acne is one of the most common skin problems among adolescents and can affect self-confidence and quality of life. Many adolescent students perform self-medication for acne without sufficient knowledge about proper drug selection and usage. This community service activity aimed to improve knowledge and self-medication behavior toward acne through skin health education among adolescent students at Al-Istiqomah Islamic Boarding School, Garut. The method used included pretest and posttest questionnaires to assess the level of knowledge and behavior, followed by interactive counseling using presentation materials and educational leaflets. A total of 68 adolescent students participated in this activity. The results showed an increase in students’ knowledge and behavioral changes in choosing appropriate acne treatment products. The educational intervention was proven effective in improving knowledge and promoting more rational acne self-medication behavior among adolescent students at the boarding school (p < 0.05).